Efisiensi Pemasaran Kacang Tanah (Arachis hypogeae L) Di Kelurahan Landasan Ulin Tengah Kecamatan Landasan Ulin Kota Banjarbaru Provinsi Kalimantan Selatan - Zuraida Zuraida; Yayuk Minta Wahyuningsih (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
Spot transactions peanut producers and consumers in the Village is the cornerstone of Middle Ulin Pasar Jaya subdistrict Platform Ulin there are two patterns of distribution channels, with the level distribution pattern of the biggest marketing margin on institutions village traders at $ 2,600 (44.82%) while the two patterns Rp 3,800 (71.70%). while the level of marketing efficiency in both the pattern is efficient because the marketing pattern of the index amounted to 32.72 Economical efficiency greater than Technical Efficiency Index of 28.35, while the marketing pattern of two Economical efficiency Index 34 is also larger than the Technical Efficiency Index of 33.0.